Efektivitas Penggunaan M-Learning Dalam Pembelajaran Interaksi Sosial - Ai Faridawaty (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
The aim of this study was to reveal the effectiveness of using m-learning in social science learning, especially about social interaction. The researcher used a quantitative research design in this research. The participants of this study were 30 students of SMPN 1 Wanaraja. The research instruments in this study were pre-test and post-test. The researcher utilized SPSS as the data analysis application. The result of this study showed that the use of m-learning in social science learning, especially in social interaction was effective